Examining the longevity of trade partnerships: A duration analysis of Ethiopia’s international trade flows - Abiyot G. Gebre; Amsalu Dachito Chigeto (PLoS ONE, 2026)
This study examines the longevity of Ethiopia’s trade partnerships duration and its determinants using a survival analysis. While the existing literature extensively studies the determinants of trade volume, this study uniquely investigates how long bilateral trade ties persist and what determines their duration, with particular emphasis on Ethiopia. Employing bilateral export data from 1997 to 2023, combined with gravity-based variables and rich institutional and macroeconomic indicators, the analysis applies random effect parametric survival estimates to capture the timing and risk of trade relationship dissolution. We find that initial export volumes and institutional quality significantly enhance trade longevity, Geographic proximity exhibits significant effects: shared borders are associated with longer trade durations, whereas longer distance shortens the duration. While Ethiopia’s own-economic size correlates with shorter trade survival, larger partner economies tend to sustain longer trade relationships. Moreover, regional dynamics reveal that Sub-Saharan African partners demonstrate greater persistence in trade links. The findings carry important policy implications for fostering sustainable trade growth and economic resilience in Ethiopia and comparable economies, underscoring the importance of strengthening institutions, upgrading infrastructure, and cultivating cooperative regional arrangements to reinforce durable trade partnerships.